TRIANGLE OF POLITICAL POWER OF THE MATARAMAN COMMUNITY IN KEDIRI - Taufik Alamin (Program Studi Sosiologi Agama Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2022)
The political upheaval in the early days of reform had an impact on the formation of parties which were no longer monopolized by the political elites during the New Order era. This was evidenced by the democratic principle of transparency in the election of government officials. The development of the political culture at the regional level is different from the situation at the national level. The development of political culture at the regional level is more dominated by political thoughts and behavior based on a mature political culture. The Mataraman Kediri community has social and cultural characteristics that also influence their political traditions. In the context of general elections, the Mataraman community has a special characteristic in their political choices which is reflected in the choice and support for certain political parties, that the way the people elect depends on their past historical patterns. The results of this study indicate that the people of Mataraman Kediri have a synergistic political pattern known as thearchitecture of power politics. The relationship between the religious elite, entrepreneurs, and the government has a political synergy that is able to influence political patterns and maps in the Mataraman region of Kediri.